2017
DOI: 10.1111/jen.12373
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of trapping systems for monitoring of Afrotropical fruit flies

Abstract: The efficacy of different attractant trap combinations for monitoring of Afrotropical fruit flies was evaluated in commercial fruit production areas and natural areas in the northern parts of South Africa. Five food‐based attractants: three‐component Biolure, a combination of ammonium acetate and trimethylamine, a combination of ammonium acetate and putrescine, torula yeast and Questlure, were evaluated in McPhail‐type traps. Two male lures targeting Ceratitis species: EGO Pherolure and trimedlure, were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
3
31
1
Order By: Relevance
“…It can be seen that fruit fly species richness was influenced by the host plant diversity in plant formations. Similar results were obtained by Manrakhan et al (2017) who pointed out that the diversity of tephritid species was higher in natural environments than in commercial orchards in South Africa. According to Geurts et al (2012), the diversity of fruit fly species in a biotope depended on the diversity of the host fruit.…”
Section: Fruit Fly Species Richness According To Plant Formationssupporting
confidence: 88%
See 1 more Smart Citation
“…It can be seen that fruit fly species richness was influenced by the host plant diversity in plant formations. Similar results were obtained by Manrakhan et al (2017) who pointed out that the diversity of tephritid species was higher in natural environments than in commercial orchards in South Africa. According to Geurts et al (2012), the diversity of fruit fly species in a biotope depended on the diversity of the host fruit.…”
Section: Fruit Fly Species Richness According To Plant Formationssupporting
confidence: 88%
“…According to Geurts et al (2012), the diversity of fruit fly species in a biotope depended on the diversity of the host fruits. Manrakhan et al (2017) stated that plant formations around mango orchards play a major role in fruit fly population dynamics. By taking these three types of plant formations into account, this study provides a better understanding of the role of each plant formation in the emergence and maintenance of fruit fly pests through its floristic composition.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was found that, all four treatments showed marked selectivity for females. This results coincides with the findings of (Manrakhan et al, 2017), who found that significantly more C. capitata females were trapped in three-component Biolure-baited Chempac Bucket trap (AA + TMA + PT) than in other lures (a combination of AA + TMA, a combination of AA + PT, torula yeast and Questlure in McPhail-type traps. In the same trend Ben Jemâa et al, (2010) found that the percentage of captured C. capitata females was significantly higher than that of males in mandarin and washengton navel orange orchards.…”
Section: Discussionsupporting
confidence: 91%
“…Traps with male attractants such as trimedlure generally gave a better picture of medfly spatio-temporal dynamics than Biolure, but do not catch mated females, that are responsible for larval infestations. As several food-based attractants have been investigated in recent years [ 61 63 ], we believe an important challenge will be to specifically assess the monitoring of mated females. In fact, treating females as a whole can produce unreliable results, as unmated females and mated females have very different spatial distribution patterns in some periods.…”
Section: Discussionmentioning
confidence: 99%